Azrael [videorecording (DVD)] - Barrett, Simon; Weaving, Samara, 1992-; Sonne, Victoria Carmen, 1994-; Stewart-Jarrett, Nathan, 1985-; Willestrand, Vincent; Tamel, Mart; Baudhun, Ben; Þórarinn Guđnason (Shudder ; IFC Films, 2025)
In a world where no one speaks, a devout female hunts down a young woman who has escaped her imprisonment. Recaptured by its ruthless leaders, Azrael is due to be sacrificed to pacify an ancient evil deep within the surrounding wilderness.